Strategi kolaborasi lembaga keuangan dan usaha mikro, kecil, dan menengah dalam meningkatkan keberlanjutan usaha: Studi literatur - Karyanto, Rania Annisa' (Maliki Interdisciplinary Journal, 2024)
MSMEs in Indonesia have contributed significantly to the national economy but face challenges such as limited access to financing, lack of managerial skills, and minimal marketing networks. This research explores collaboration between MSMEs and financial institutions as a solution to improve business sustainability. Using a literature review method, this study analyzes various programs launched by governments and financial institutions including credit guarantee and entrepreneurship training as well as the importance of digitalization to improve market access. The findings show that this collaboration not only helps MSMEs overcome existing obstacles but also strengthens their capacity through financial education, technological innovation, and the use of digital platforms. This study recommends that the government and financial institutions expand products and services that suit the needs of MSMEs, especially in rural areas. By creating policies that support collaboration between sectors and strengthen support networks, MSMEs can increase their competitiveness and contribute more to local and national economic growth. This research provides new insights for stakeholders in designing more effective programs in supporting the sustainability of MSMEs.